Identifying Essential Features of Juvenile Psychopathy in the Prediction of Later Antisocial Behavior: Is There an Additive, Synergistic, or Curvilinear Role for Fearless Dominance?. (May 2016) - Vize, Colin E.; Lynam, Donald R.; Lamkin, Joanna; Miller, Joshua D.; Pardini, Dustin
Despite years of research and the inclusion of psychopathy in DSM-5, there remains debate over the fundamental components of psychopathy. Although there is agreement about traits related to agreeableness and conscientiousness, there is less agreement about traits related to fearless dominance (FD) or boldness. The present article uses proxies of FD and self-centered impulsivity (SCI) to examine the contribution of FD-related traits to the predictive utility of psychopathy in a large, longitudinal sample of boys to test four possibilities: FD (a) assessed earlier is a risk factor, (b) interacts with other risk-related variables to predict later psychopathy, (c) interacts with SCI interact to predict outcomes, and (d) bears curvilinear relations to outcomes. SCI received excellent support as a measure of psychopathy in adolescence; however, FD was unrelated to criteria in all tests. It is suggested that FD be dropped from psychopathy and that future research focus on agreeableness and conscientiousness.